2015
DOI: 10.1371/journal.pone.0140813
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Attentional Bias towards Attractive and Unattractive Body Regions among Overweight Males and Females: An Eye-Movement Study

Abstract: BackgroundBody image distortion is highly prevalent among overweight individuals. Whilst there is evidence that body-dissatisfied women and those suffering from disordered eating show a negative attentional bias towards their own unattractive body parts and others’ attractive body parts, little is known about visual attention patterns in the area of obesity and with respect to males. Since eating disorders and obesity share common features in terms of distorted body image and body dissatisfaction, the aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 68 publications
2
23
1
1
Order By: Relevance
“…In comparing the findings to past research, consistency can be found despite the use of different methodologies (Cho & Lee, 2013;Cordes et al, 2017;Warschburger et al, 2015). Cho and Lee (2013) and Cordes et al (2017) found that men with high body dissatisfaction gazed longer at stimuli considered muscular and attractive.…”
Section: Associations Between Attentional Biases and Body Imagesupporting
confidence: 55%
See 1 more Smart Citation
“…In comparing the findings to past research, consistency can be found despite the use of different methodologies (Cho & Lee, 2013;Cordes et al, 2017;Warschburger et al, 2015). Cho and Lee (2013) and Cordes et al (2017) found that men with high body dissatisfaction gazed longer at stimuli considered muscular and attractive.…”
Section: Associations Between Attentional Biases and Body Imagesupporting
confidence: 55%
“…Indeed, in another sample of men who were regular resistance exercisers (N = 49), Cordes et al (2017) found that those who gazed for longer durations towards disliked parts of their own body demonstrated poorer body image and mood post exposure. However, attention to one's own attractive regions may also reflect an APPEARANCE-RELATED ATTENTIONAL BIASES 8 attentional avoidance pattern in that attractive regions are favored to avoid distress felt about unattractive regions (Warschburger et al, 2015). Although the behavioral eye-tracking measures indicate attentional allocation is on attractive body regions, the nature of the thoughts accompanying the behavior is unclear.…”
mentioning
confidence: 99%
“…The only observer-BMI-related difference in the current study was that OB spent less time exploring natural body stimuli than normal-weight participants. This could be interpreted as a visual avoidance pattern in order to reduce discomfort [10]. The avoidance of natural stimuli might serve as self-value protection function [38].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have investigated the attentional processing of individuals with eating disorders [8,9] and obesity [10] of their own bodies. Most of these studies investigated the allocated attention to body parts that participants had previously classified as ‘ugly' versus ‘beautiful'.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation